DSPs court the consumer. - Eyre, J. (IEEE spectrum)
A new breed of consumer product draws on advanced audio compression and decompression schemes made practical by digital signal processors. The choices of particular algorithms and processors for specific products are examined for three innovative products: digital home audio, for downloading audio from the Internet for real-time playback, and for phone calls using the voice-over-Internet protocol